Estimating the deployment costs of broadband universal service via fiber networks in Korea. (May 2021) - Lee, Hyeongjik; Jeong, Seonkoo; Lee, Kwanghee
Abstract: While both broadband itself and its speed are becoming increasingly important in all spheres of society, the high cost of providing broadband as a universal service at high speed still raises a fundamental question: Is the introduction of the universal service obligation (USO) necessary? Therefore, the introduction of universal broadband service at 100 Mbps in Korea in 2020 could be a meaningful case study to evaluate the necessity of broadband USO. This study proposes an estimation model of the costs of providing universal broadband service in Korea and assesses whether the introduction of the broadband USO was appropriate in Korea. Since the proposed model was based on the bottom-up (BU) approach, which establishes an efficient network using the latest technologies, the estimated cost of providing universal broadband service nationwide in Korea is accurate and reliable. The main findings are threefold. First, the total cost of providing broadband USO at 100 Mbps through the fiber-to-the-home technology was about 1.1 trillion Korean Won. Since this is a relatively small amount compared with previous evaluations, it could be recovered within a reasonable period from the monthly broadband fee that subscribers pay. Therefore, the result supports the introduction of universal broadband service in Korea. Second, there was no significant difference in the average cost per building for broadband USO between 50 Mbps and 100 Mbps; thus, the Korean government's decision to set the broadband speed for broadband USO at 100 Mbps was reasonable, at least from a cost perspective. These results imply that developed countries with relatively high broadband penetration, in particular, could consider providing universal broadband services of at least 50 Mbps by fiber-based technologies. Lastly, although the total cost of offering fiber-based universal broadband services in Korea was acceptable, the government could also consider including wireless access technology as a technological alternative to reduce the costs of the USO policy. Highlights: The paper proposes a cost estimation model for Korea's universal broadband service. The model was used to evaluate whether the deployment in Korea was appropriate. The results support the introduction of the universal broadband service in Korea. We find that fiber-based technologies are the most cost-efficient in Korea. Governments could also consider wireless access as an alternative to reduce costs.